Dietary Pterostilbene Inhibited Colonic Inflammation in Dextran-Sodium-Sulfate-Treated Mice: A Perspective of Gut Microbiota. Issue 1 (8th March 2021) - Li, Fang; Wang, Qi; Han, Yanhui; Song, Mingyue; Cai, Xiaokun; Goulette, Timothy; Xiao, Hang
Abstract : Abstract: Dietary interventions based on the use of bioactive nutraceuticals might offer an effective adjuvant therapeutic and preventive method for inflammatory bowel disease by reshaping colitis-associated bacterial dysbiosis. The current study aimed to determine the anti-inflammatory effect of pterostilbene (PTE, a methylated derivative of resveratrol) and its potential modulatory roles in gut microbiota in a dextran sodium sulfate (DSS)-induced colitis mouse model. Our results supported our hypothesis that dietary PTE exerted protective effects against colonic inflammation; evidenced by the reduced colonic tissue damage, decreased disease activity index, and lowered production of pro-inflammatory cytokines such as interferon gamma, interleukin (IL)-2, IL-4, and IL-6 in the colon of DSS-treated mice. Moreover, α-diversity analysis indicated that dietary PTE significantly improved gut microbial evenness and diversity. Noteworthy, PTE modified gut microbiota composition toward a healthier profile by boosting the richness of Bifidobacterium and decreasing the distribution of pathogenic Bilophila and Rc4-4 . Pearson correlation analysis also revealed strong associations between the shifting of gut microbiota and expression of inflammatory cytokines in the colon. Overall, our study demonstrated that dietary PTE alleviated the severity of colitis in DSS-treated mice and gut microbiota may play an indispensable role in this process mechanistically.